Hubungan Antara Work Overload dan Lingkungan Kerja Terhadap Stress Kerja pada Karyawan - Wahyuningsi; Ruby, Arcivid Chorynia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The purpose of this study is to investigate how employees' stress levels are influenced by their work environment and workload. Data is gathered using a scale as part of a quantitative research methodology. After removing outliers, 94 respondents were chosen from 136 employees to make up the sample. The analysis's findings indicate that job stress, work overload, and work environment are significantly correlated (R = 0.274, p = 0.029). Significant relationships were also found between job stress and work environment (R = 0.273, p = 0.004) and between job stress and work overload (R = 0.244, p = 0.009). According to the study's findings, the primary causes of work-related stress are excessive workloads and unfavourable working conditions. Employee performance is impacted by the physical and psychological imbalances brought on by work stress. It is recommended that employers manage workload sensibly, establish a supportive work atmosphere, and encourage the use of mindful living to increase employee well-being. The focus on respondents who suffer from work-related stress and the online data collection are two of the study's limitations. As a result, it is hoped that additional research will broaden the study to include additional factors that influence work-related stress.